PROFIL ANTROPOMETRI DAN KEBUGARANKARDIORESPIRASI PADA MAHASISWA ANGKATAN2016/2017 FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO - Maharani Reswari K.; Ari Udiyono; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Easinesses in doing activity, that causes mobility of movement, has decreased. Physical activity requires to be improved in order to advance cardiorespiratory fitness. The purpose of this study was to recognise differences in body weight, height, BMI, waist circumference and cardiorespiratory fitness of the students in the class of 2016/2017 when attending lectures and a year later. This type of research is quantitative research. The sample of research is students in the class of 2016/2017, Faculty of Public Health, Diponegoro University, numbered as many as 39 people. Samples were taken based on exclusion and inclusion criteria. Based on the results of research in 2017, the average of weight is 68,58 ± 15,22. The average of height is 169,48 ± 6,50. The average of indeks of body mass is 23,94 ± 5,44. The Average of waist circumference is 84,94 ± 15,81. The average of cardiorespiratory fitness is 37,01 ± 6,04. Data analyzed using Paired t test with α = 0,05 indicates there is a difference in height (p = 0,000). Wilcoxon signed rank test results with α = 0,05 prove that there is a difference in body weight (p = 0,000), difference in indeks of body mass (p=0,000), a difference in waist circumference (p = 0,000) and difference in cardiorespiratory fitness (p = 0,025). Suggestion of research of fitness improvement activity is making the routine sport programs like: low impact aerobic gymnastics, running and walking for health together at least once a month with all academic community.